Capitalizing on big data and revolutionary 5G technology: Extracting and visualizing ratings and reviews of global chain hotels. (October 2021) - Gaur, Loveleen; Afaq, Anam; Solanki, Arun; Singh, Gurmeet; Sharma, Shavneet; Jhanjhi, N.Z.; My, Hoang Thi; Le, Dac-Nhuong
Abstract: This paper aims to use machine learning (ML) algorithm for natural language pre-processing (NLP), text mining (TM), and sentiment analysis (SA) techniques to analyze and examine 45, 500 online reviews of customers of 50 global chain hotels from different online review sites. Furthermore, the paper addresses the new business value and experiences that the revolutionary 5G technology can bring to the hotel industry. The research findings revealed that the general review star rating corresponds with the opinion (sentiment) scores for the title and the full substance of the online reviews. The case study's contextual analysis also uncovered that both fulfilled and disappointed customers have a frequent inclination for five categories: food, stay, rooms, service, and staff. This study contributes both theoretically and practically to the multidisciplinary domains of computer science, information systems, and tourism and discovers hidden patterns in data using visual analytics techniques. Graphical abstract: Highlights: Role of Machine Learning is applied to examine analyze online reviews of customers from global chain hotels. Sentiment and category interpretation aids in projecting the emerging trends and insights of hotel industry. The implementation of 5G technology and machine learning can bring a massive boost to the hotel industry. Potentiality to digitalize the hotel industry more rapidly and embrace new business models.